Large Vallecula Lipoma: An unusual clinical entity (Bangladesh Journal of Medical Science, 2016)
Lipoma of the oropharynx is an extremely rare entity with less than ten cases reported in so far. We present the case of a 55-year-old gentleman who was referred to our team for an incidental finding of an oropharyngeal mass. Although he did not have stridor despite the mass occupying almost 80% of his oropharynx, he did complain of progressive voice change, feeling of something in the throat and dysphagia over a period of 2 years. The mass was successfully excised endoscopically without the need for a tracheostomy. Airway issues, management options of an oropharyngeal mass, as well as the applied embryology of these lesions are discussed. Bangladesh Journal of Medical Science Vol.15(4) 2016 p.621-623